2019
DOI: 10.1039/c9nj02833a
|View full text |Cite
|
Sign up to set email alerts
|

Silver-mediated radical phosphorylation/cyclization of N-allylbenzamides to access phosphoryl-substituted dihydroisoquinolones

Abstract: A silver-mediated phosphorylation/cyclization of N-allylbenzamides with phosphine oxides for the synthesis of phosphoryl-substituted dihydroisoquinolones was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Later, Liu and co-workers reported a method for the efficient synthesis of a variety of phosphoryl-substituted dihydroisoquinolones from methacryloylbenzamides and P(O)H compounds via a silver-mediated reaction (Scheme 50). 58 Different silver salts and solvents were screened, and the results showed that AgNO 3 was the best oxidant and CH 3 CN was the most effective solvent. The amount of AgNO 3 was investigated, and the results indicated that 2 equivalents of silver salt were required in this reaction.…”
Section: Reviewmentioning
confidence: 99%
“…Later, Liu and co-workers reported a method for the efficient synthesis of a variety of phosphoryl-substituted dihydroisoquinolones from methacryloylbenzamides and P(O)H compounds via a silver-mediated reaction (Scheme 50). 58 Different silver salts and solvents were screened, and the results showed that AgNO 3 was the best oxidant and CH 3 CN was the most effective solvent. The amount of AgNO 3 was investigated, and the results indicated that 2 equivalents of silver salt were required in this reaction.…”
Section: Reviewmentioning
confidence: 99%
“…Although a pioneering radical amino-phosphorylation of unactivated alkenes of 2-allylanilines toward 2-phosphonomethyl-N-sulfonyl indolines has been established by Zhang et al [24] , the development of an economical method from readily available materials remains highly desirable. In 2018, Liang et al [25] developed a silver-catalyzed radical arylphosphorylation of unactivated alkenes via a cascade phosphorylation-arylation sequence [Figure 9]. This protocol displays a broad substrate scope, high exo/endo selectivity and simple operation, with a diverse array of 3-phosphonoalkyl indolines obtainable in satisfactory yields.…”
Section: Intramolecular Carbophosphorylationmentioning
confidence: 99%
“…A gram‐scale synthesis could also be readily carried out by the authors. One year later, Chen, Sun, Yu and co‐workers aslo developed similar phosphorylation/cyclization strategy between N ‐allylbenzamides with phosphine oxides to accomplish the phosphoryl‐substituted dihydroisoquinolones consturcted [34] . Compared with Liang's alkene substrates, they used the carbon chain growth substrates with one more carbon atom (Scheme 30).…”
Section: Silver‐mediated Two‐component Alkene Functionalization Reactmentioning
confidence: 99%